2009
DOI: 10.1097/wnr.0b013e32832a2c63
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of thyroid hormone receptor β2 protein in cone photoreceptors in the mouse

Abstract: Thyroid hormone receptor β2 (TRβ2) controls the patterning of cone opsin photopigments that mediate colour vision. We raised an antiserum against TRβ2 to study cone photoreceptor development by western blot and immunostaining analyses. TRβ2-positive cells first appeared between embryonic day 10 (E10) and E12. Numbers increased until near birth, correlating with generation of the cone population. At birth, signals decreased until postnatal day 10 (P10), then declined to very low levels in adulthood. TRβ2-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 22 publications
4
65
0
Order By: Relevance
“…Several previous studies have demonstrated TR expression in the vertebrate retina (Sjöberg et al, 1992;Harpavat and Cepko, 2003;Mader and Cameron, 2006;Applebury et al, 2007;Ng et al, 2009;Raine and Hawryshyn, 2009). Both TRa and TRb are expressed in the retina of another fish, the winter flounder (Pleuronectes americanus), in addition to rainbow trout (Mader and Cameron, 2006;Raine and Hawryshyn, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated TR expression in the vertebrate retina (Sjöberg et al, 1992;Harpavat and Cepko, 2003;Mader and Cameron, 2006;Applebury et al, 2007;Ng et al, 2009;Raine and Hawryshyn, 2009). Both TRa and TRb are expressed in the retina of another fish, the winter flounder (Pleuronectes americanus), in addition to rainbow trout (Mader and Cameron, 2006;Raine and Hawryshyn, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…TH signaling regulating cone viability is likely mediated via TRβ2, which, in the retina, is expressed only in cones (33,34). T3-induced cone death did not occur in Thrβ2 −/− mice, and cone degeneration caused by deficiency of type 3 iodothyronine deiodinase (DIO3, an enzyme that inactivates T3) was rescued in Dio3 −/− /Thrβ2 −/− mice (12).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, similar to S-opsin mRNA, TR␤2 expression may be topographically rearranged in a manner leaving total retinal transcript level(s) of TR␤2 unaltered. It is not yet established whether during early development cone-specific expression of TR␤2 is dorsoventrally graded (Fujieda et al, 2009) or not (Roberts et al, 2005;Applebury et al, 2007), and available methodology appears to lack sufficient sensitivity to resolve the spatiotemporal characteristics of Tr␤2 expression in the adult retina with cellular precision (Applebury et al, 2007;Ng et al, 2009) (our own attempts with riboprobes), likely because of low TR␤2 levels present. Future efforts therefore should evaluate TR␤2 expression in the wild-type compared with the hypothyroid adult retina.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse early postnatal development, thyroid hormone (TH), through its receptor TR␤2, is an important regulator of cone spectral identity by repressing S-opsin and activating M-opsin (Ng et al, 2001;Roberts et al, 2006;Applebury et al, 2007;Pessô a et al, 2008;Lu et al, 2009, Glaschke et al, 2010. In the adult retina, however, the role of TH signaling in opsin regulation is unclear, despite an abundance of hormone (Ientile et al, 1984;Roberts et al, 2006) and the persistent, albeit low expression of TR␤2 in cones (Applebury et al, 2007;Fujieda et al, 2009;Ng et al, 2009). …”
Section: Introductionmentioning
confidence: 99%